2015
DOI: 10.1016/j.micres.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Alternative sigma factor RpoN2 is required for flagellar motility and full virulence of Xanthomonas oryzae pv. oryzae

Abstract: Xanthomonas oryzae pv. oryzae (Xoo), the bacterial blight pathogen of rice, harbors a single polar flagellum for motility. How the flagellar system is regulated and how it is related to bacterial pathogenesis are not well understood. The genomic sequence of Xoo strain PXO99(A) revealed a flagellar regulon containing over 60 contiguous genes. A gene encoding alternative sigma factor 54 (σ(54)), named as rpoN2, is located in the central region of the regulon. RT-PCR analysis demonstrated rpoN2 was transcribed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(88 citation statements)
references
References 50 publications
1
86
0
Order By: Relevance
“…It has also been revealed that some bacteria, including Xanthomonas oryzae pv. oryzae, Bradyrhizobium japonicum, Rhizobium etli, Burkholderia fungorum, and Ralstonia solanacearum, carry two copies of rpoN (31)(32)(33)(34), and four copies of rpoN are encoded in the genome of Rhodobacter sphaeroides (35). The four paralogues were designated rpoN1, rpoN2, rpoN3, and rpoN4, and their GϩC contents were 68.29%, 68.48%, 69.57%, and 56.13%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been revealed that some bacteria, including Xanthomonas oryzae pv. oryzae, Bradyrhizobium japonicum, Rhizobium etli, Burkholderia fungorum, and Ralstonia solanacearum, carry two copies of rpoN (31)(32)(33)(34), and four copies of rpoN are encoded in the genome of Rhodobacter sphaeroides (35). The four paralogues were designated rpoN1, rpoN2, rpoN3, and rpoN4, and their GϩC contents were 68.29%, 68.48%, 69.57%, and 56.13%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Combined estimated means and SE are presented, as well as the difference between the means and the P values for each pairwise statistical contrast. (Lee et al, 2003;Tian et al, 2015). Using a Raspberry Pi-controlled camera, images of the plates were taken for several days, and the area of bacterial spread was quantified (Supplemental Fig.…”
Section: Characterizing Bacterial Spread In Vitromentioning
confidence: 99%
“…Like many other Xanthomonads, Xoo harbors a single-polar flagellum, which is required for its swimming motility [20]. The flagellin protein is encoded by a fliC gene, which is located in the middle of a large flagellar regulon consisting of approximately 60 genes [20].…”
Section: Introductionmentioning
confidence: 99%
“…The flagellin protein is encoded by a fliC gene, which is located in the middle of a large flagellar regulon consisting of approximately 60 genes [20]. Although the motility driven by flagella has been shown to be an important virulence factor in several bacterial species, we have recently demonstrated that the flagellar motility of Xoo does not contribute to its virulence directly [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation